Evidence for metaviromic islands in marine phages - Mizuno, Carolina M.; Ghai, Rohit; Rodriguez-Valera, Francisco (Frontiers in Microbiology, 2014)
Metagenomic islands have been defined as genomic regions in prokaryotic genomes that under-recruit from metagenomes where most of the same genome recruits at close to 100% identity over most of its length. The presence of metagenomic islands in prokaryotes has been associated to the diversity of concurrent lineages that vary at this level to disperse the predatory pressure of phages that, reciprocally, maintain high clonal diversity in the population and improve ecosystem performance. This was proposed as a Constant-Diversity (C-D) model. Here we have investigated the regions of phage genomes under-recruiting in a metavirome constructed with a sample from the same habitat where they were retrieved. Some of the genes found to under-recruit are involved in host recognition as would be expected from the C-D model. Furthermore, the recruitment of intragenic regions known to be involved in molecular recognition also had a significant under-recruitment compared to the rest of the gene. However, other genes apparently disconnected from the recognition process under-recruited often, specifically the terminases involved in packaging of the phage genome in the capsid and a few others. In addition, some highly related phage genomes (at nucleotide sequence level) had no metaviromic islands. We speculate that the latter might be generalist phages with broad infection range that do not require clone specific lineages.